Development Strategy for Talang Semut Areas as a Heritage Tourism Destination in Palembang - Danindra Atharikusuma (Program Pascasarjana Universitas Sriwijaya, 2022)
Talang Semut in the city of Palembang was designed by Thomas Karsten during the Dutch East Indies administration as a garden city for Palembang residents of European descent. In addition to a settlement, public and urban social facilities, including churches, hotels, swimming pools, and retention pools to prevent flooding, were constructed in this area. The architecture of the buildings in Talang Semut is distinct from local architecture due to the influence of Indies architecture and modern architecture (de Stijl). As a historic district in Palembang, Talang Semut continues to expand and attract increasing numbers of tourists. The general public, especially building owners, does not correctly comprehend the growth of the Talang Semut neighborhood, which undermines its status as a historic district. In addition, there is no clear direction or strategy for preserving and promoting Talang Semut as a heritage tourism attraction. This study aims to examine initiatives to prevent harm and loss of historical significance and the creation of heritage tourism sites. Observation, interviews, documentation, and questionnaires are used to collect data for this descriptive quantitative study. The results of this study reveal that the community does not see Talang Semut as a heritage region that must be maintained in addition to its development as a tourism attraction. Land conversion and building facade modifications will continue. This study concludes that immediate technical and non-technical measures must be taken to prevent damage to the Talang Semut region. In addition to a more organized management structure, the Talang Semut area must be directed to enhance and add supporting amenities to become a heritage tourism destination.